Controllable growth of Au@TiO2 yolk–shell nanoparticles and their geometry parameter effects on photocatalytic activity. (28th June 2017) - Sun, Hang; He, Qinrong; Zeng, Shan; She, Ping; Zhang, Xiaochen; Li, Jiayi; Liu, Zhenning
Abstract : The one-pot hydrothermal approach has been used to achieve Au@TiO2 yolk–shell NPs with different geometry parameters: smaller cavities, thinner TiO2 shells and medium Au cores facilitate more efficient photocatalysis. Abstract : Yolk–shell nanoparticles (NPs) have attracted significant interest due to their decreased reflection and high solar light utilization. Herein, we precisely and independently controlled the geometrical parameters of the cavity diameter, shell thickness, and Au core diameter in the Au@TiO2 yolk–shell NPs using the hydrothermal method. Furthermore, the photocatalytic activities of these samples were systematically evaluated by the photocatalytic degradation of Rhodamine B (RhB). Smaller cavity size, thinner TiO2 shell, and medium AuNP diameter were found to facilitate more efficient photocatalysis. Overall, Au@TiO2 yolk–shell NPs with a cavity diameter of 121 nm, Au core diameter of 50 nm, and shell thickness of 26 nm demonstrated highest photocatalytic activity. These results are important for understanding the effects of the geometrical parameters of Au@TiO2 yolk–shell NPs on the photocatalytic performance and for designing novel yolk–shell nanostructures.